2018
DOI: 10.3389/fimmu.2018.02795
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in the Aging Liver and Age-Related Liver Disease

Abstract: The number of individuals aged 65 or older is projected to increase globally from 524 million in 2010 to nearly 1. 5 billion in 2050. Aged individuals are particularly at risk for developing chronic illness, while being less able to regenerate healthy tissue and tolerate whole organ transplantation procedures. In the liver, these age-related diseases include non-alcoholic fatty liver disease, alcoholic liver disease, hepatitis, fibrosis, and cirrhosis. Hepatic macrophages, a population comprised of both Kupffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(82 citation statements)
references
References 160 publications
(194 reference statements)
2
79
1
Order By: Relevance
“…Hepatic macrophages exert a crucial role in the pathogenesis of various chronic liver diseases 7–9 . As resident macrophages in the liver, Kupffer cells can undergo a wide range of phenotypic and functional switching depending on the environmental stimuli they receive.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic macrophages exert a crucial role in the pathogenesis of various chronic liver diseases 7–9 . As resident macrophages in the liver, Kupffer cells can undergo a wide range of phenotypic and functional switching depending on the environmental stimuli they receive.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, numerous reviews are available on the crucial roles of hepatic macrophages in liver cancer, (7)(8)(9) fibrosis, (6,10,11) alcoholic liver disease and bacterial infections, (12)(13)(14)(15)(16) nonalcoholic fatty liver disease, (17)(18)(19) viral hepatitis, (20) cholestatic diseases, (21,22) drug-induced acute liver injury, (23,24) ischemia reperfusion injury and liver transplant, (25,26) liver regeneration, (23,27,28) and also in aging liver. (29) Because our knowledge on macrophages in the context of liver disease has increased exponentially over recent years, a fresh view on this fascinating immune cell population has emerged, challenging some old dogmas and highlighting the heterogeneity and plasticity of liver macrophages.…”
mentioning
confidence: 99%
“…Besides cognitive and motor performance, ATP-dependent immune responses of macrophages reduce in aged animals [15,16], which are particularly at risk for developing chronic diseases. We have identified that exogenous mitochondria are not able to enter red blood cells because the cells lack endocytic function [ 17 ].…”
Section: Mitotherapy Increased Phagocytosis Of Macrophagesmentioning
confidence: 99%